The crystal structure of (E)-4-chloro-N′-(1-(4-hydroxyphenyl)propylidene)benzohydrazide, C16H15ClN2O2 - Wang Yanjiao; Wang Chao; Gao Xuguang; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C16H15ClN2O2, triclinic, P1‾$P\overline{1}$ (no. 2), a = 7.9715(8) Å, b = 8.2727(8) Å, c = 11.5105(12) Å, α = 90.296(8)°, β = 100.566(9)°, γ = 102.603(9)°, V = 727.41(13) Å3, Z = 2, Rgt(F) = 0.0522, wRref(F2) = 0.1257, T = 293 K.